Adélie penguin population changes at Stranger Point: 19 years of monitoring. Issue 5 (20th May 2015) - Juáres, Mariana A.; Santos, Mercedes; Negrete, Javier; Mennucci, Jorge A.; Perchivale, Pablo J.; Casaux, Ricardo; Coria, Néstor R.
Abstract: The Adélie penguin ( Pygoscelis adeliae ) breeding population at Stranger Point, King George Island (25 de Mayo), increased in number from 1965/66 until 1980/81 after which it started to decrease almost continuously up to the present. A significant decrease in the number of breeding pairs and chicks crèched was observed between 1995/96 and 2013/14 (75% and 78%, respectively), although the rate of this decrease has slowed since 2006/07. Over the last seven years, larger interannual fluctuations were recorded in the number of breeding pairs and chicks in crèches, as well in the breeding success. The values for the index of breeding success during 2007/08, 2009/10 and 2012/13 were low and this parameter showed higher temporal fluctuation in the period 2007/08 to 2013/14. The reduction in breeding success and the number of chicks reared to crèche will unfavourably impact on future population size at Stranger Point through the reduction of new recruits. Although Adélie penguin population trends on the Antarctic Peninsula are linked to the marine environment variability (i.e. reduction in sea ice affecting the availability of prey), breeding success is also influenced by the amount of snow fall which has increased in recent years.